Penerapan Teknik Level-Based Gameplay Game 2D Adventures Of Tim Untuk Platform Android Menggunakan Unity - Adytia, Rangga; Faisal, Ilham (Jurnal Ilmu Komputer dan Sistem Komputer Terapan (JIKSTRA), 2025)
ABSTRACT The goal to be achieved in this final assignment is to design and create a game entitled Adventure that can be run on a smartphone. This is motivated by the high interest of game players. By using this trend the author will create a level-based adventure themed game that challenges the player's interest. Using level-based techniques, the author will create a game that is oriented towards a level system where at each level visuals from various maps will be presented that are challenging, interesting and exciting. This research designs and develops the Adventures of Tim game with level-based gameplay techniques using Unity, with the integration of elements and visual designs that are attractive to casual gamers aged 10–40 years. The development method for making this adventure- themed game was built using the Multimedia Development Life Cycle (MDLC) system development method with six stages, namely: concept, design, material collection, manufacture, testing and distribution. By using the method above, a game platform will be created that will run on Android. This game will be made in Unity and the C# programming language is the script. By making this game, the author also hopes that it will be an aid and reference for further research that applies level-based games in making games.